A generic tool wear model and its application to force modeling and wear monitoring in high speed milling. (15th January 2019) - Zhu, Kunpeng; Zhang, Yu
Highlights: Established a generic tool flank wear model with adjustable coefficients. Identified the relationship of the critical times to the adjustable coefficients in the model. Defined a method to predicate tool life with the wear model. Compared and validated milling forces per tooth obtained both from the model and the experimental data. Abstract: Tool wear is an important factor that influence machining precision and part quality in high speed milling, and it is essential to seek a convenient method to monitor and predict tool conditions. A generic wear model with adjustable coefficients is proposed and validated in this study. In this model, three wear zones of an entire tool life are divided by critical times considering the nature of different wear stages. Additionally, the intrinsic amplitude and growth frequencies in earlier and later milling stages are explicated and elaborated to determine the tool flank wear over whole milling process. The relationship between milling force against tool flank wear is studied and identified, which provides a technical foundation for online force modeling and wear monitoring. It is shown that with inclusion of the wear factor the milling force can be predicted accurately, with 98.5% agreement with the instantaneous force model. In addition, tool life can be predicted conveniently based on the wear model. Due to adjustability of coefficients in the model, it can be generalized to various machining types and conditions.